Memerangi Api dengan Api: Menggunakan Film untuk Melawan Film Propaganda - Gary Jason (Neolectura, 2023)
His article explores how effective films are in countering propaganda in films. To organize the discussion, first a simple sketch of propaganda theory is drawn up, in which propaganda can be ranked from completely rational to highly irrational, on six different dimensions. This is how far the propaganda went: evidence-based; Honest; broadly logical; transparent; right on target; and transparent. Then the main propaganda film is reviewed in detail, Gasland. This film is a highly successful documentary attacking the production of natural gas by hydrofracturing, which is referred to in America as